2020
DOI: 10.1136/jitc-2020-000877
|View full text |Cite
|
Sign up to set email alerts
|

Host genetics and tumor environment determine the functional impact of neutrophils in mouse tumor models

Abstract: BackgroundNeutrophils have been reported to have protumor, antitumor or neutral effects in cancer progression. The underlying causes for this functional variability are not clear.MethodsWe studied the role of neutrophils in six different mouse tumor models by intratumoral injection of antimicrobial peptides or vaccination. Changes in systemic and intratumoral immune cells were analyzed by flow-cytometry and mass-cytometry. The role of neutrophils was studied by antibody-mediated neutrophil depletion. Neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Our characterization of the TME complements previous reports investigating the immune cell composition in various tumor models based on flow cytometry or RNA sequencing ( 58 , 63 65 ). Although some variations between the different studies are seen, our data is largely in line with these reports.…”
Section: Discussionsupporting
confidence: 75%
“…Our characterization of the TME complements previous reports investigating the immune cell composition in various tumor models based on flow cytometry or RNA sequencing ( 58 , 63 65 ). Although some variations between the different studies are seen, our data is largely in line with these reports.…”
Section: Discussionsupporting
confidence: 75%
“…Ly6G expression on granulocytes can be separated into Ly6G hi and Ly6G int fractions, the former of which represents a more mature cell population ( 48 ). Granulocytes expressing lower levels of Ly6C are expanded in relation to tumor growth ( 49 ). Thus, these studies suggested that increased expression of Ly6G and/or Ly6C may be indicative of granulocyte maturation.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-infiltrating tumor-reactive T cells function as a tissue-specific trigger for tumor destruction but are not always necessary 39 or sufficient 15 for tissue damage. We and others have shown that the T-cell-driven regression of tumors may require the attraction and activation of tumoricidal phagocytic macrophages 14 26 34 or neutrophils 40 to deliver the final cytotoxic insult. While neutrophils display antitumor activity in the TC-1 model, 40 we showed here that they do not contribute to the efficacy of therapeutic vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that the T-cell-driven regression of tumors may require the attraction and activation of tumoricidal phagocytic macrophages 14 26 34 or neutrophils 40 to deliver the final cytotoxic insult. While neutrophils display antitumor activity in the TC-1 model, 40 we showed here that they do not contribute to the efficacy of therapeutic vaccination. The requirement of T cells to deliver the trigger and macrophages to fully execute the cytotoxic program in cancer cells fits well with the concept of programmed cell removal, linking programmed cell death to the removal of the dying cell.…”
Section: Discussionmentioning
confidence: 99%